Sumber Daya Manusia dalam Perspektif Pendidikan Islam - Munawwir Munawwir; Khoirun Nikmah; Silvi Syarifatun Nuroniyah (Departement of Mathematics Education, 2023)
The decline of the Islamic religion is a new phase in the change of Human Resources. During the Jahiliyya period, the condition of society was not yet developed and was very bad, both in interactions with the Creator and in interactions with other people. Humans are not only determined by aspects of skills, abilities or physical strength, but must have standards as well as education or levels of knowledge, experience and attitudes or values. The complexity of problems in education, causing educational problems and the need to improve the quality of human resources must ensure that educational problems remain attractive to them in the hope that alternative solutions will emerge through Islamic education in improving the quality of human resources.